Injuries caused by the venomous catfish pintado and cachara (Pseudoplatystoma genus) in fishermen of the Pantanal region in Brazil - De Aquino, Giuliano N. R.; De Souza, Celso C.; Haddad Junior, Vidal [UNESP]; Sabino, Jose (Acad Brasileira De Ciencias, 2016)
INTRODUCTION: the fishing activity throughout the Upper Paraguay River Basin has huge financial and biological importance. This retrospective study investigated the occurrence of injuries caused by fish of the Pseudoplatystoma genus (spotted catfish or pintado and striped catfish or cachara) in professional fishermen of the Pantanal of Mato Grosso do Sul State. METHODS: we collected information through a questionnaire, showing that fishing is carried out by workers with low level of education, mainly adults or seniors with low financial gains. RESULTS: in Miranda town, 126 of 315 fishermen were interviewed and 38 individuals reported injuries (30.16%). In Corumba town, 355 of 627 fishermen were interviewed, and 111 (56,61%) reported injuries. The lacerated lesions were the most common, associate with edema, erythema, radiating pain to the root of the limb, paresthesias and local necrosis. More rarely, they reported the occurrence of fever, cardiac arrhythmias and cold sweating. These manifestations may be associated with late secondary infections or envenomations caused by the toxins in the stingers of the fish. Many questionable and inappropriate treatments are used, sometimes aggravating the injuries. CONCLUSIONS: the freshwater professional fishermen need guidance on first aid measures and prevention of accidents caused by these venomous fish.
Keywords: Pantanal; Spotted catfish; Striped catfish; Pseudoplatystoma; professional fishermen; Public Health